An Examination that Involves Analysis and Comparison of Cognitive Abilities within the Context of Both Sports and Non-Sports Persons - Vikramjeet; Singh, Parambir (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Study Aim: This study aimed to investigate the difference in cognitive abilities between sports and non-sports persons. Material and Methods: A total of 110 school-aged children participated in this cross-sectional study, comprising 40 sports persons and 70 non-sports persons. Cognitive ability was assessed using the Cognitive Abilities Test (CAT–SVSP), developed by Vishal Sood and Pooja Sharma. Statistical Analysis: Unpaired t-test was employed for the present investigation. Results: The results showed no significant difference in cognitive ability scores between sports persons (M = 47.85, SD = 5.8675) and non-sports persons (M = 47.84, SD = 5.23). The t-value was 0.0066, which was below the critical value of 1.984, indicating no significant difference.